An Exceptionally Preserved Terrestrial Record of LIP Effects on Plants in the Carnian (Upper Triassic) Amber-Bearing Section of the Dolomites, Italy - Roghi, Guido; Gianolla, Piero; Kustatscher, Evelyn; Schmidt, Alexander R.; Seyfullah, Leyla J. (Frontiers in Earth Science, 2022)
The Carnian Pluvial Episode (CPE) has been recognized as a time of plant radiations and originations, likely related to observed swift changes from xerophytic to more hygrophytic floras. This suggests that the increasing humidity causally resulting from LIP volcanism was the trigger for these changes in the terrestrial realm. Understanding the cause and effects of the CPE on the plant realm, requires study of well-preserved floras that are precisely aligned with the CPE. We therefore focus on the best age-constrained section within the CPE for the terrestrial to marginal marine environment to understand the floristic composition at the early CPE. This is found in the Dolomites, Italy and is remarkable for the preservation of the oldest fossiliferous amber found in the rock record. An integrated study of palynomorphs and macro-remains related to the conifer families of the fossil resin bearing level brings together the floral components from this section. This observed mixture of different taxa of extinct and modern conifer families underlines firmly the effects of the LIP-induced CPE on the evolution and radiation of conifers.